New Design of Solar Photovoltaic and Thermal Hybrid System for Performance Improvement of Solar Photovoltaic. (15th July 2020) - Hossain, Ridwone; Ahmed, Al Jumlat; Islam, Sheik Md Kazi Nazrul; Saha, Nirupam; Debnath, Preetom; Kouzani, Abbas Z.; Mahmud, M. A. Parvez
Abstract : Solar photovoltaic (PV) and solar thermal systems are most widely used renewable energy technologies. Theoretical study indicates that the energy conversion efficiency of solar photovoltaic gets reduced about 0.3% when its temperature increases by 1°C. In this regard, solar PV and thermal (PVT) hybrid systems could be a solution to draw extra heat from the solar PV panel to improve its performance by reducing its temperature. Here, we have designed a new type of heat exchanger for solar PV and thermal (PVT) hybrid systems and have studied the performance of the system. The PVT system has been investigated in comparison with an identical solar PV panel at outdoor condition at Dhaka, Bangladesh. The experiments show that the average improvement of open circuit voltage (Voc) is 0.97 V and the highest improvement of Voc is 1.3 V. In addition, the overall improvement of output power of solar PV panel is 2.5 W.